2006
DOI: 10.1371/journal.ppat.0020128
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous MMTV Proviruses Induce Susceptibility to Both Viral and Bacterial Pathogens

Abstract: Most inbred mice carry germline proviruses of the retrovirus, mouse mammary tumor virus (MMTV) (called Mtvs), which have multiple replication defects. A BALB/c congenic mouse strain lacking all endogenous Mtvs (Mtv-null) was resistant to MMTV oral and intraperitoneal infection and tumorigenesis compared to wild-type BALB/c mice. Infection of Mtv-null mice with an MMTV-related retrovirus, type B leukemogenic virus, also resulted in severely reduced viral loads and failure to induce T-cell lymphomas, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Other mechanisms of resistance to lymphocyte infection and virus spread include a hyperimmune antibody response that occurs in I/LnJ mice and increased viral clearance by T cells in YBr/Ei mice (8,9,33). The lymphoid tissues of mice lacking endogenous copies of the MMTV provirus are also resistant to MMTV infection, although the mechanism for this resistance is not known (5,6). Here, we examined 19 different inbred mouse strains and found that there are two alleles of the mA3 gene with regard to exon 5 and the surrounding introns.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms of resistance to lymphocyte infection and virus spread include a hyperimmune antibody response that occurs in I/LnJ mice and increased viral clearance by T cells in YBr/Ei mice (8,9,33). The lymphoid tissues of mice lacking endogenous copies of the MMTV provirus are also resistant to MMTV infection, although the mechanism for this resistance is not known (5,6). Here, we examined 19 different inbred mouse strains and found that there are two alleles of the mA3 gene with regard to exon 5 and the surrounding introns.…”
Section: Discussionmentioning
confidence: 99%
“…Sag is a transmembrane glycoprotein that is involved in the lymphocyte-mediated transmission of MMTV from maternal milk in the gut to susceptible epithelial cells in the mammary gland (5,6). The Sag protein expressed by endogenous (germline) MMTV proviruses has been reported to provide susceptibility to infection by exogenous MMTVs or the bacterial pathogen, Vibrio cholerae (7). These results suggest a role for MMTV Sag in the host innate immune response.…”
mentioning
confidence: 99%
“…A recent study has shown that endogenous MMTV SAg expression can increase susceptibility to infection by a range of bacterial and viral pathogens through an unidentified mechanism (45). Potentially, HERV-K18 SAg may exert similar properties.…”
Section: Herv-k and Melanomamentioning
confidence: 99%